Quasi one dimesional metal oxide nanostructures for chemical sensing application - Singh, Nandan (2012)
Quasi one dimensional (1D) nanostructures are potential candidates to meet the challenges for the realization of future sensors. They offer many advantages over thin film based sensors such as higher crystallinity, high surface-to-volume ratio, low power consumption, long channel with small cross sectional area which controls the conductance. In this thesis, the properties of metal oxides (MOx) nanowires in a field effect transistors (FET) configuration are studied. Mainly the electronic and chemical sensing properties of In2O3 based nanowires have been established. Quasi 1D nanostructures are synthesized in horizontal tube CVD furnace based on VLS mechanism. Different morphologies are obtained by varying the growth conditions such as; growth temperature, pressure and growth duration. In2O3 nanowires (with diameters of 25-90 nm and length of 10-50 m), nanotowers (with diameter 100-150 nm and length below 10 m) and long layered nanorods (with a diameter of 200-400 nm and length of 20-50 m) are grown through carbothermal reduction of In2O3 powder by varying source temperature in a CVD horizontal furnace. VLS-VS competitive growth is proposed for the formation of layered nanorods at higher source temperature. As deposited nanowire samples on alumina substrates are used as a gas sensor. Pristine In2O3, Zn-doped In2O3 and In2O3-ZnO core shell nanowires are used to test various pollutant gases under the resistor configuration. Such devices have shown optimum sensor response at higher working temperature. It is observed that pristine In2O3 nanowires have shown better sensor response towards NO2 gas while Zn-doped In2O3 and 2 In2O3-ZnO core shell nanowires have shown superior sensor response for ethanol, H2, CO and acetone (reducing gases). Nanowire FET (NW-FET) devices are fabricated on highly doped Si substrate using SiNx as gate dielectric layer and bottom gate configuration. Photolithography process is used to design the microelectrodes for NW-FET device. Further, gas sensing mechanism on single and network nanowire sensors is investigated by comparing doped and undoped, Ohmic and Schottky contact devices. A highly sensitive device for CO gas sensing at room temperature is fabricated using gold nanoparticle functionalization. High coverage of gold nanoparticles on nanowire channel is obtained using a self assembled monolayer of p-amino-phenyl-tri-methoxy-silane. The sensor response for CO gas is observed to be depending on gold nanoparticle coverage. It is observed that devices with Schottky contacts, Zn doping and core-shell hetero-structures have shown improved sensor response for reducing gases (e.g. CO, H2, ethanol, acetone etc.) in contrast to the pristine nanowires and devices with Ohmic contact. Schottky contact devices have shown a better sensor response for reducing gases and Ohmic contact devices have shown a better sensor response for oxidizing gases. Similarly In2O3-ZnO core shell hetero-structures have shown better response for reducing gases (e.g. CO, H2, and ethanol). Highly sensitive NW-FET devices are fabricated by understanding the role of contact resistance. We have developed highly sensitive devices operating at room temperature by utilizing the contact resistance and coupling it with the nanowire channel functionalization with Au nanoparticles. This work provides a promising approach to fabricate room temperature working devices with excellent sensing capabilities.